Eigenvalue-based signal detectors performance comparison - Omar, Mohd Hasbullah; Hassan, Suhaidi; Awang Nor, Shahrudin (2011)
The purpose of this paper is to compare the performance of eigenvalue-based signal detectors designed for IEEE 802.22 Wireless Regional Area Network (WRAN). Two eigenvalue techniques were studied, which are the eigenvalue decomposition (EVD) and singular value decomposition (SVD) Both techniques were implemented on Matlab as detection algorithms.Using Monte Carlo simulations, we tested the algorithms to compare their performance. We also adopted the maximum-minimum eigenvalue threshold method as the decision statistic for detecting signals. The tests were done for their ability to detect signal, receiver operating characteristics, expected performance, robustness and computational complexity. Empirically, the performance of SVD technique found to be better compared to the EVD technique.